PRIMARY SCHOOL TEACHERS’ READINESS ON THE USE OF AI GENERATED IMAGE TO TEACH LITERATURE IN ACTION COMPONENT - Muhammad Farhan Mohd.Yazid; Azlina Abdul Aziz (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
This study investigates the readiness of primary school teachers to use AI-created images for teaching literature, identifying the main factors influencing such readiness. For this research, a sample of 70 teachers will be approached. The study will be carried out by applying various statistical analyses: reliability analysis, descriptive statistics, correlation analysis, and regression analysis. The results indicate that teachers’ readiness is high and significantly influenced by performance expectancy, effort expectancy, social influence, and facilitating conditions. These factors have a positive correlation with teachers’ readiness to accept AI-generated images, which is further testified by regression analysis as having predictive power. The implications of these findings are great in terms of educational policy, teacher training, curriculum development, and technology integration for stipulating the need for supportive policies, comprehensive training programs, and user-friendly AI tools in the teaching process. The proposed future studies are longitudinal in nature, such as investigating teacher readiness, the impact of AI on student learning outcomes, cross-cultural comparison studies, and various applications of AI in education. This research study thus adds value to the burgeoning literature on AI integration into schools and paves the way for subsequent studies toward improving teaching practices and enhancing.